ANALISIS EFISIENSI DAN EFEKTIVITAS PENGELOLAANKEUANGAN KABUPATEN SIDOARJO TAHUN 2022,2023 DAN 2024 - Grace Victress Gabriel Belen; Ria Ekanindya Widyaningsih (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyze the eficiency and efectiveness of financial management in the Sidoarjo Regency Government during the fiscal years 2022, 2023, and 2024. A descriptive quantitative approach was employed by calculating eficiency and efectiveness ratios based on budget realization reports. The results show that the level offinancial eficiencyfluctuated: it was classified as highly ineficient in 2022 (107.66%),fairly eficient in 2023 (83.88%), and less eficient in 2024 (98.46%). Meanwhile, the level of efectiveness showed positive performance, with very efective outcomes in 2022 (101.18%) and 2024 (104. 77%), and moderately efective results in 2023 (81.07%). These findings indicate improvements in financial governance in terms of eficiency and stability in achieving regional revenue targets. The results are in line with the theory of eficiency by Mahmudi (2016), which emphasizes the optimal use of resources to produce maximum output, and the theory of efectiveness by Mardiasmo (2009), which highlights the achievement of planned objectives. Therefore, the financial management of Sidoarjo Regency is considered to be improving and increasingly aligned with the principles of good governance in public financial management.